The Lord of the Rings the two towers
The fellowship has broken, but the quest to destroy the one ring continues, Frodo and Sam must entrust their lives to Gollum if they are to find their way to Mordor. As Saruman's army approaches, the surviving members of the fellowship, along with people and creatures from Middle-earth, prepare for battle. The war of the Ring has begun.